Expanstines A–D: four unusual isoprenoid epoxycyclohexenones generated by Penicillium expansum YJ-15 fermentation and photopromotion. Issue 23 (17th October 2019) - Wang, Jia-Peng; Shu, Yan; Liu, Shi-Xi; Hu, Jun-Tao; Sun, Cheng-Tong; Zhou, Hao; Gan, Dong; Cai, Xue-Yun; Pu, Wei; Cai, Le; Ding, Zhong-Tao
Abstract : Expanstines A–D from P. expansum YJ-15 were derived under UV and visible light from 4′-oxomacrophoin A (5 ) and its acetate (6 ), which plausibly underwent a rare intramolecular photoene reaction and a [2 + 2] Paternò–Büchi photoaddition respectively. Abstract : Two new isoprenoid epoxycyclohexenones, expanstines A–B (1–2 ), and two novel isoprenoid epoxycyclohexenones, expanstines C–D (3–4 ), featuring an unusual oxetane ring were isolated from Penicillium expansum YJ-15. Their structures were initially investigated in detail by NMR spectroscopy, HRESIMS, XRD and ECD experiments. Expanstines A–D were derived under UV and visible light from 5 and 6, which plausibly underwent a rare intramolecular photoene reaction and a [2 + 2] Paternò–Büchi photoaddition respectively. Both 3 and 4 exhibited potent antibacterial activities against B. subtilis, with an MIC of 0.25 μg mL −1 .